A Critical Case Study of Teacher Education Student Created Memes - Sarah Swafford; Gary Padgett (Undergraduate Research Journal for the Human Sciences, 2016)
From Facebook to Twitter, social media has introduced the world to memes. Memes are an innovative way to express an opinion or show true feelings without feeling pressured to answer in a certain way. The methodology related to using internet memes has been around for almost 20 years (Downes, S., 1999; Heylighen, F., 1996; Knobel, M., & Lankshear, C., 2007), but no one has yet combined it with the field of education research. Colleges of Education are already reaching out to students via Twitter and Instagram, so using memes to gather information from students is a logical next step. This article demonstrates how this has been done to improve teacher education programs.
Keywords: Teaching; Memes